(untitled) (Revista Direito em Debate, 2022)
The present article analyzes the case of Dominic Ongwen, a member of the armed group Lord’s Resistance Army, who had been recruited as a child to the group in the context of the Ugandan armed conflict and who had committed the same violation he suffered in the past, being accused in the International Criminal Court. Thus, on the macro level, the influence of European imperial/colonial past to international law is emphasized just as how it leads to the creation and continuity of hostilities. And at the micro level, in the light of the subalternity generated by such a system, this study aims at understanding the phenomenon of coercive capture of child soldiers during armed conflicts and its consequences on their psyche, pointing, after all, to the need to revisit the vicious cycle of illegality and imperiality that forms and characterizes the international order for a more precise analysis of the case and the rules of the Tribunal. Hence, methodologically, this study of applied nature will follow the hypothetical-deductive method of approach, establishing a relationship between Gayatri Spivak thoughts and the case of Uganda, passing through the construction of ICC and the rules regarding the use of child soldiers during hostilities – points that will be explored by the descriptive and explanatory method and whose references will be obtained from two bibliographic and documental procedures, following a qualitative approach, however, without aiming to exhausting them.